2016
DOI: 10.2147/jhc.s86708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of vascular endothelial growth factor in hepatitis C related hepatocellular carcinoma in Egyptian patients

Abstract: Background and aimsSeveral angiogenic factors are involved in the development and progression of hepatocellular carcinoma (HCC), a hypervascular tumor. Vascular endothelial growth factor (VEGF) is a primary driving force for angiogenesis, and its overexpression has been reported in HCC. However, the significance of plasma and tissue VEGF levels in HCC in Egyptian patients with chronic hepatitis C (CHC) infection is understudied. The aim of this study was to evaluate the role of VEGF (measured in plasma and liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
9
2
2
Order By: Relevance
“…Li et al, postulated that VEGF can enhance portal vein thrombosis formation in HCC by influencing the angiogenesis process [43]. On the other hand, we did not find a significant correlation between the serum VEGF levels and the number of hepatic focal lesions in contrast to other researchers [24,44] where VEGF accelerates vascular permeability which increases the release of malignant cells into the circulation [45].…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Li et al, postulated that VEGF can enhance portal vein thrombosis formation in HCC by influencing the angiogenesis process [43]. On the other hand, we did not find a significant correlation between the serum VEGF levels and the number of hepatic focal lesions in contrast to other researchers [24,44] where VEGF accelerates vascular permeability which increases the release of malignant cells into the circulation [45].…”
Section: Discussioncontrasting
confidence: 97%
“…In our study, we found that serum VEGF levels strongly correlated with serum AFP which agrees with other studies [24,46,47], and this supports the prognostic value of both VEGF and AFP in HCC patients [47]. According to the relationship between VEGF and liver function tests, we did not find significant correlations between them in both the HCC group and HCV liver cirrhosis group which agrees with the results obtained by Atta et al [24], where they postulated that VEGF expression cannot be considered as an indicator of the liver synthetic function or the inflammatory state which eliminates the possibility that inflammatory process has an impact on VEGF expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is one of the most common types of carcinoma and is characterized by an enriched blood supply. The progression of angiogenesis is vital for tumour occurrence and development and is closely associated with HCC metastasis, invasion and resistance to therapy ( 5 , 6 ). Thus, several anti-angiogenic drugs (such as sorafenib) have been recommended for clinical applications as treatment options for patients with advanced stage HCC ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HCV is considered a major public health problem in Egypt. Complications of HCV infection in Egypt are responsible for 67% of morbidity related to liver disease (Atta et al, 2016). Patients with chronic HCV are at risk of developing cirrhosis which may be followed by hepatocellular carcinoma (HCC), .…”
Section: Introductionmentioning
confidence: 99%